Staff Views Towards the Sexuality of Adults with Mild Intellectual and Developmental Disabilities: The Role of Experience and Job Position - Ana Belén Correa; Ángel Castro; María Dolores Gil-Llario (Sexes)
Staff attitudes towards the sexuality of adults with mild intellectual and developmental disabilities may influence how the sexuality of service users is dealt with. The present study aimed to examine these attitudes in a Spanish context. A total of 102 staff members from service facilities for adults with intellectual and developmental disabilities, including direct-care and professional staff, responded to an online version of the Attitudes Towards the Sexuality of Individuals with Intellectual Disabilities Scale. In general, the participants demonstrated an understanding that adults with intellectual and developmental disabilities have sexuality. They reported favourable attitudes towards some self- and other-oriented sexual behaviours and sex education. Intermediate scores and variability on some items revealed concerns about these adults’ ability to control their sexual urges, perceptions of sexual abuse, pornography use, and contraception. Some differences appeared in relation to socio-demographic variables, experience and job position. Although generally favourable, differences in dispositional attitudes, such as talking about sexuality, were related to years of experience in the field. Professional staff reported greater acceptance of some sexual behaviours compared to direct-care staff. These findings are relevant to understanding variability in staff perceptions. The need for support to respond to service users’ sexuality, especially among direct-care professionals, is discussed.